1988
DOI: 10.1111/j.1570-7458.1988.tb01184.x
|View full text |Cite
|
Sign up to set email alerts
|

L‘élevage de deux coccinelles Harmonia axyridis et Semiadalia undecimnotataà l'aide d'oeufs d’Anagasta kuehniella tués aux rayons ultraviolets

Abstract: R~sum~Les coccinelles aphidiphages Harmonia axyridis Pallas et Semiadalia undecimnotata Schneider (Coccinellidae) ont 6t6 61ev6es pendant trois g6n6rations ~t raide d'oeufs d'Anagasta kuehnieila Zell. (Pyralidae) tu6s par une exposition hun rayonnement ultraviolet. Chez la premiere esp6ce, cette proie de substitution pr6sente une valeur alimentaire comparable sice nest pas sup6rieure ~ celle du puceron Acyrthosiphonpisum (Harris). Ces r6sultats permettent d'envisager, d~s ~t pr6sent, une production massive dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 11 publications
(9 reference statements)
0
29
1
Order By: Relevance
“…Secondly, natural populations of close relatives of H. axyridis have been reported to exploit beetle larvae as their principal prey (e.g., Whitehead & Duffield, 1982;Elliott & de Little, 1990). Finally, females of H. axyridis reproduce well on other non-aphid foods [powder of drone honey bees (Niijima et al, 1988) and eggs of Lepidoptera (Schanderl et al, 1988;Abdel-Salam & Abdel-Baky, 2001;Michaud, 2002)]. …”
Section: Discussionmentioning
confidence: 99%
“…Secondly, natural populations of close relatives of H. axyridis have been reported to exploit beetle larvae as their principal prey (e.g., Whitehead & Duffield, 1982;Elliott & de Little, 1990). Finally, females of H. axyridis reproduce well on other non-aphid foods [powder of drone honey bees (Niijima et al, 1988) and eggs of Lepidoptera (Schanderl et al, 1988;Abdel-Salam & Abdel-Baky, 2001;Michaud, 2002)]. …”
Section: Discussionmentioning
confidence: 99%
“…The polyphagous species C. maculata, for example, produces very large numbers of eggs in the laboratory when it feeds on eggs of the Colorado potato beetle, Leptinotarsa decemlineata (Say) (Hazzard & Ferro, 1991;Munyaneza & Obrycki, 1997) or the European corn borer, Ostrinia nubilalis (Hubner) (Phoofolo & Obrycki, 1997), foods that it is known to feed on in natural settings. Harmonia axyridis (Pallas) produces eggs at high rates when fed eggs of the lepidopteran Ephestia (Anagasta) kuehniella Zeller (Schanderl et al, 1988). The prey is a pest of stored products that this predator would not encounter naturally, but its reproductive response may reflect that it does often exploit similar prey as well as aphids in nature.…”
Section: Additional Questionsmentioning
confidence: 99%
“…Laboratory tests have shown that it is a powerful biological agent for use against many phytophagous species. That this ladybird beetle can be successfully reared on the eggs of Ephestia kuehniella Zeller (Schanderl et al, 1988) makes it easy to produce in large number for inundative releases. However, its negative impact on native ladybird beetles and other non-target arthropods is rarely studied (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…It is a very polymorphic ladybeetle in which some of the phenotypes differ in fitness (Soares et al, 2001(Soares et al, , 2003. This euryphagous predator prefers aphids (Hukusima & Kamei, 1970;Iablokoff-Khnzorian, 1982;Osawa, 1992), but can feed on psyllids (Fye, 1981;Drea & Gordon, 1990), coccids (McLure, 1987;Hodek & Hon k, 1996), immature stages and eggs of Lepidoptera (Schanderl et al, 1988;Drea & Gordon, 1990) and spider mites (Drea & Gordon, 1990;Lucas et al, 1997a). Laboratory tests have shown that it is a powerful biological agent for use against many phytophagous species.…”
Section: Introductionmentioning
confidence: 99%